Unilateral Vulvar Pneumatocele (Pneumolabium) Diagnosed during Robotic Hysterectomy - Dani Zoorob; Mahala Spalsbury; Tiffany Slutz; Madeleine Oliver; Ibrahim Tsolakian; Jeffrey Judis (Case Reports in Obstetrics and Gynecology)
Background. Persistent canal of Nuck may manifest in adulthood and be detected after increased abdominal pressure. Case. A 52-year -old female undergoing a robotic hysterectomy developed an acute left labial enlargement. The patient was discovered to have an 8 × 4 × 4 cm swelling in the left labium majus. Palpation revealed the mass to be air-filled and reducible by gentle compression with slow redevelopment upon release of the pressure while intra-abdominal insufflation was maintained. Conclusion. We present the first case of a labial pneumatocele during robotic hysterectomy. We theorize that the underlying cause to be a patent canal of Nuck that, once supplied with increasing abdominal peritoneal pressure, allowed air to travel into the labia majora through the inguinal canal. Simple reduction corrected the pneumatocele and no complications or recurrence was noted postop. This case suggests that pathologies of the canal of Nuck should be considered in the differential of an adult presenting with inguinal or genital swelling.